Comparison of blood glucose levels in breastfed vs. formula-fed low birth weight infants - Eli Tua Pangaribuan; Bugis M. Lubis; Pertin Sianturi; Emil Azlin; Guslihan D. Tjipta (Paediatrica Indonesiana, 2009)
Background  Low  birth weight infants are defined  as  babies withbirth weight less  than  2500 grams.  Low  birth weight infants tendto suffer from hypoglycemia compared to full term infants.  Theincidence  of  hypoglycemia in newborns varies between 1.3 and  3per 1000 live births. Blood glucose levels in formula-fed infantsare lower  than  those in breastfed infants.Objective  To  compare blood glucose levels in breastfed  andformula-fed low birth weight infants.Methods  A cross sectional study was conducted between February2007  and  June 2007  at  Pirngadi and H. Adam Malik GeneralHospital in Medan,  North  Sumatra, Indonesia. All low birthweight babies were classified into two groups: the breastfed  andformula-fed. Each group consisted  of  32 infants. Capillary bloodwas collected using heel pricks  at  1,  48,  and  72 hours after birth,and plasma glucose was evaluated using the Glucotrend2 bloodglucose test.Results  The  breastfed low birth weight infants had significantlyhigher blood glucose levels (P=0.002)  than  formula-fed low birthweight infants. Mode of delivery  was  related to blood glucose level.Infant delivered  by  caesarean section had significantly differentblood glucose levels  at  1 hour  (P=0.005)  and  72  hours afterbirth (P=0.027).  The  full-term infants had significantly higherblood glucose level (P=0.007)  than  the small for gestational ageinfants.Conclusions  Generally,  low  birth weight infants have hypoglycemiaafter first hour  of  delivery. Breastfed low birth weight infants havehigher blood glucose levels  than  formula-fed low birth weightinfants.